The Role of Organization-Based Self-esteem and Organizational Communication toward Job Involvement in Research Center Organization - Romadona, Mia Rahma (Jurnal Pekommas, 2018)
Research institutions as well as other organizations have core business in science and technology research and development have many external and internal constraints to actively engage their researchers. Internal problems that become obstacles faced by research institutions is that individual productivity is not the same as the productivity of the organization, so there is a distance that becomes the factors causing the researcher's job involvement on organization. The purpose of research is to see the relationship between organization-based self-esteem (OBSE) and organizational communication with job involvement in a research institute to increase science and technology productivity. The research question is how the role of organization-based self-esteem towards the job involvement and how the role of organizational communication to the job involvement of researchers in X institution research. We used mix method by quantitative approach of relationship analysis to measure organization-based self-esteem with the job involvement, while to see organizational communication with job involvement with qualitative case study approach. The results obtained that organization-based self-esteem has been shown to be significantly associated with the job involvement of researchers in research institutions. In addition, organizational communication also affects the job involvement of researchers in research institutions. It shows that individual factors can collectively impact on organizational success in achieving the targets.